Engineering the optical properties of dielectric nanospheres by resonant modes. (12th October 2018) - Ullah, Kaleem; Huang, Lujun; Habib, Muhammad; Liu, Xuefeng
Abstract: Recent progress in nanoscale optical physics is associated with the development of a new branch of nanophotonics exploring strong Mie resonances in dielectric nanoparticles with high refractive index (HRI). The high-index resonant dielectric nanostructures form building blocks for novel photonic meta-devices with low losses and advanced functionalities. In this work, we investigate the size effect of an HRI cuprous oxide (Cu2 O) nanosphere on the optical properties of the structure, such as, scattering and absorption spectrum. We also experimentally demonstrate that the scattering field can be significantly engineered by tuning the radius of Cu2 O. It is found that the resonant eigenmodes supported by the nanospheres play the dominant role in the absorption and scattering characteristic of the structure. From the perspective of eigenmodes, we can immediately find the right structure parameters to realize strong absorption (scattering) at either single wavelength or broadband wavelength. Furthermore, the multipole expansion method has been applied to explore the physical nature (i.e. electric mode or magnetic mode) of the eigenmode as well as contributions from different modes.